This problem is from OMO.
For reals x ≥ 3 , let f ( x ) denote the function f ( x ) = 2 − x + x 4 x − 3 . Suppose a 1 , a 2 , . . . , a 2 0 1 3 is a sequence of real numbers such that a 1 > 3 , a 2 0 1 3 = 2 0 1 3 , and for n = 1 , 2 , . . . , 2 0 1 2 , a n + 1 = f ( a n ) . Determine the value of a 1 + i = 1 ∑ 2 0 1 2 a i 2 + a i a i + 1 + a i + 1 2 a i + 1 3
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Verify that a i 3 = a i 2 + a i a i + 1 + a i + 1 2 , so
i = 1 ∑ 2 0 1 2 a i 2 + a i a i + 1 + a i + 1 2 a i + 1 3 − i = 1 ∑ 2 0 1 2 a i 2 + a i a i + 1 + a i + 1 2 a i 3 = i = 1 ∑ 2 0 1 2 ( a i + 1 − a i ) = a 2 0 1 3 − a 1 .
Since i = 1 ∑ 2 0 1 2 a i 2 + a i a i + 1 + a i + 1 2 a i 3 = 2 0 1 2 , the desired answer is thus 2 0 1 3 + 2 0 1 2 = 4 0 2 5 .
Problem Loading...
Note Loading...
Set Loading...
Let A = a 1 + i = 1 ∑ 2 0 1 2 a i 2 + a i a i + 1 + a i + 1 2 a i + 1 3 = a 1 + i = 1 ∑ 2 0 1 2 a i 2 + a i a i + 1 + a i + 1 2 a i + 1 3 − a i 3 + a i 3
= a 1 + i = 1 ∑ 2 0 1 2 ( a i + 1 − a i ) + i = 1 ∑ 2 0 1 2 a i 2 + a i a i + 1 + a i + 1 2 a i 3
The first sum is solved using telescoping series property to get − a 1 + a 2 0 1 3 .
We have f ( x ) = 2 − x + x 4 x − 3 and a i + 1 = f ( a i ) .
x 2 + x f ( x ) + f ( x ) 2 = x 2 + f ( x ) ( x + f ( x ) ) = x 2 + f ( x ) ( x + 2 − x + x 4 x − 3 )
= x 2 + 2 − x + x 4 x − 3 2 x + x 4 x − 3
= x 2 + 4 − 4 x 2 + 4 x 3 = x 3 = > a i 2 + a i a i + 1 + a i + 1 2 = a i 3 (let x = a i )
= > A = a 1 − a 1 + a 2 0 1 3 + i = 1 ∑ 2 0 1 2 1 = 2 0 1 3 + 2 0 1 2 = 4 0 2 5